Briefly Noted. (Chronicle of Higher Education, 1979)
The article presents news briefs related to higher education in the United States. Texas Christian University at Fort Worth asserts that it is the first institution to offer a graduate program in computer programming leading to the degree Master of Software Engineering. The Department of Health, Education and Welfare may seek a $500,000 refund from Indiana University officials.